Language Crafted A Linguistic Theory of Poetic Syntax - Austin, Timothy R. (Indiana University Press, 1984)
Stylistics is at a crossroad, according to Timothy Austin. It must find a way of bridging the chasm that separates it from deconstructionism and a means of restoring the faith of disillusioned stylists, like Stanley Fish and his followers, in its precepts. Offering a new, comprehensive, and clearly articulated theory of stylistics, Language Crafted is a first-and giant-step toward the goal of the revitalization of stylistics. Austin sets out the standards that a general theory of stylistics must meet. It must delimit its range of phenomena; it should offer a well-defined theoretical model, complete with theoretical categories and a description of the ways those categories relate to one another; it must evaluate the capacity of the model to analyze data in an approp- riate and elegant way; and it should examine the implications of its conclusions for associated fields. Using these standards, Austin outlines a linguistic theory of poetic syntax, elaborating on its provisions and extending its exemplifications to cover a broad spectrum of authors and texts. Austin's refreshing approach to poetic syntax offers great hope for a positive and productive future for the discipline of stylistics.